Are the methylenetetrahydrofolate reductase 1298 and 677 gene polymorphisms related to optic glioma and hamartoma risk in neurofibromatosis type 1 patients? - Tanyıldız, Hikmet Gülşah; Yeşil, Şule; Bozkurt, Ceyhun; Çandır, Mehmet Onur; Akpınar-Tekgündüz, Sibel; Toprak, Şule; Yüksel, Deniz; Şahin, Gürses (The Turkish Journal of Pediatrics, 2016)
The methylenetetrahydrofolate reductase (MTHFR) gene plays a key role in carcinogenesis through its effects on DNA synthesis and methylation and also has a significant role in the etiology of many disorders, such as diabetes, migraine, and cardiovascular disease. Neurofibromatoses (NF) are autosomal dominant inherited diseases that can affect tissues such as bone and skin and predispose individuals to tumor development in various parts of the nervous system or body. Optic nerve glioma and brain tumors are common in children with NF, and leukemia and lymphoma incidence is also higher than normal. We therefore aimed to investigate the possible relationship between the MTHFR gene polymorphism and accompanying tumors such as neurofibroma, hamartoma, and optic glioma in children with NF1 found to have the MTHFR 677 and MTHFR 1298 gene polymorphism in this study. We included 55 pediatric patients diagnosed with NF1 between 2005 and 2014 in the study group. The control group included 44 healthy subjects without acute or chronic disease findings. A significant relationship was found between the MTHFR A1298C polymorphism and the incidence of optic glioma (p=0.014) (AA vs. AC: OR 11, 95% CI 1.27-95.17; AA vs. CC: OR 7.33, 95% CI 0.35-150.70). We also found a significant relationship between the MTHFR C1298C polymorphism and the incidence of hamartoma (p=0.019) (AA vs. AC: OR 2.12, 95% CI 0.662-6.809; p=0.203). Epilepsy incidence was high in subjects with MTHFR C677C. The MTHFR A1298C, C1298C, and C677C gene polymorphisms can be associated with a higher optic glioma, hamartoma, and epilepsy incidence, respectively, in patients diagnosed with neurofibromatosis type 1.